2022
DOI: 10.3390/ijms23031456
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis Mechanisms, Structural Models, and Photothermal Therapy Applications of Top-Down Carbon Dots from Carbon Powder, Graphite, Graphene, and Carbon Nanotubes

Abstract: In this study, top-down syntheses of carbon dots (CDs) from four different carbon precursors, namely, carbon nano powders, graphite, graphene, and carbon nanotubes, were carried out. Systematic study demonstrated that the optical properties and surface functionalities of the CDs were quite similar and mainly influenced by the synthesis method, while the sizes, morphologies, chemical compositions, and core structures of the CDs were heavily influenced by the carbon precursors. On the basis of these studies, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 52 publications
2
27
0
Order By: Relevance
“…33 The top-down approach involves breaking down, decomposing and reducing the size of large precursors such as carbon black or graphene oxide to reach the desired nanostructure size. 34,35 Top-down methods commonly used are laser ablation, arc discharge, and electrochemical oxidation. The top-down method provides significant advantages, especially in terms of controllable and uniform CLNMs size.…”
Section: Carbon-based Luminescent Nanomaterials: Preparation and Opti...mentioning
confidence: 99%
“…33 The top-down approach involves breaking down, decomposing and reducing the size of large precursors such as carbon black or graphene oxide to reach the desired nanostructure size. 34,35 Top-down methods commonly used are laser ablation, arc discharge, and electrochemical oxidation. The top-down method provides significant advantages, especially in terms of controllable and uniform CLNMs size.…”
Section: Carbon-based Luminescent Nanomaterials: Preparation and Opti...mentioning
confidence: 99%
“…Shi et al, by examining various types of carbon nanostructures, showed that quantum carbon dots did not show cytotoxic effect with the MTT test on A549 (type II pneumocytes) and HACAT (keratinocytes) cell lines at concentrations up to 1.333 mg/mL. Only for the concentration of 4 mg/mL was a decrease in the survival of A549 cells observed below 40% and HACAT up to 80% [38]. In the same study, other carbon nanostructures, such as graphene spheres and nanotubes, showed greater cytotoxicity observed at much lower concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Carbon materials, namely carbon nanotubes (CNT), carbon nanofibers (CNF), graphene, and graphitic carbon nanofiber (GNF) are extensively explored as potential support material owing to their structural benefits, high graphitic nature, and adequate surface area with high mechanical properties. Among GNFs bearing adequate porous fibrous structures, filamentary micropatterned frameworks, exposed inclines, carrier mobility, and arrangement of graphene platelets to the base-axis tends to create an extremely active ORR catalytic site and thus they are considered as an excellent support material when designing any cathode catalyst. Recently, S. Akula et al reported on GNFs and heteroatom engineering and described several types of GNFs with crystallographic alignment and morphology, viz., linear platelet, antler, cylindrical, and herringbone types, which starts a new era in developing potential corrosion resistant support material. The two-dimensional (2D) fish skeleton herringbone type structure of GNF (GNF-H) facilitates a way out for the detailed study owing to its greater electrochemical behavior as compared to other structural orientations. , Furthermore, introduction of hetero elements (such as N, B, S, P, F, etc.) on graphitic surface reports higher spin density and charge density as it brings on numerous defects and electronic charge distribution in the particle, further enhancing its catalytic activity. Moreover, boron doping takes much attention on account of its smaller atomic size and closed electronegativity with carbon and thus lowers energy barrier between them. Many researchers’ showed an interest in doping of boron on graphitic nanostructures and investigating it both experimentally and theoretically.…”
Section: Introductionmentioning
confidence: 99%